Mogroside-Rich Extract From Siraitia grosvenorii Fruits Ameliorates High-Fat Diet-Induced Obesity Associated With the Modulation of Gut Microbiota in Mice - Wang, Siyuan; Cui, Kexin; Liu, Jiahao; Hu, Jiahao; Yan, Ke; Xiao, Peng; Lu, Yangqing; Yang, Xiaogan; Liang, Xingwei (Frontiers in Nutrition, 2022)
Siraitia grosvenorii is a kind of medicinal food plant. The mogroside-rich extract (MGE) of its fruits can effectively ameliorate obesity, but the underlying mechanisms remain underexplored. In this study, we aimed to determine whether MGE can ameliorate obesity by protecting against dysbacteriosis of gut microbiota. Mice were challenged with a high-fat diet (HFD) and treated with MGE by oral gavage. Then, the characteristics of the gut microbiota were determined by 16S rDNA analysis. Our findings showed that MGE could significantly reduce body weight gain and fat tissue weight of the mice fed with HFD. Moreover, MGE markedly attenuated fatty liver, and improved glucose tolerance and insulin sensitivity. We further found that the gut microbiota structures were disturbed by HFD feeding. In particular, the abundance of Firmicutes was increased and the abundance of Bacteroidetes was decreased, resulting in an increased proportion of Firmicutes to Bacteroidetes (F/B), which contributes to obesity. Interestingly, the abnormal proportion of F/B of HFD feeding mice was restored to the level of control mice by MGE treatment. Additionally, the abundances of obesogenic microbiota, such as Ruminiclostridium and Oscillibacter were also decreased after MGE treatment. In summary, our findings demonstrate that mogroside-rich extract can modulate gut microbiota in obese mice and shed new light on how it alleviates obesity.